2000
DOI: 10.1021/jp9932315
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Decoupling in Ground and Excited States of Asymmetric Biaryls

Abstract: New asymmetric biaryls have been synthesized in order to clarify the conditions necessary for charge-transfer transitions in photoexcited neutral compounds and biradical formation in doubly charged ground-state species. A parallel behavior for both types of approaches is observed and explained with a simple coupling model allowing prediction of the intermoiety coupling strength. It is shown that for weakly coupled biaryls the monoions are connected with charge localization and the dications and dianions form t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…Pyrene boronic acid was prepared according to a reported process. [18] Compound 1 was obtained by reacting 2,7-dibromofluorene and methyl iodide with sodium tert-butoxide. 2,7-Dibromofluorenone, which was obtained by bromination of fluorenone, reacted with the Grignard reagent of bromobenzene, then dehydrated to give compound 2 with the aid of acids.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrene boronic acid was prepared according to a reported process. [18] Compound 1 was obtained by reacting 2,7-dibromofluorene and methyl iodide with sodium tert-butoxide. 2,7-Dibromofluorenone, which was obtained by bromination of fluorenone, reacted with the Grignard reagent of bromobenzene, then dehydrated to give compound 2 with the aid of acids.…”
Section: Resultsmentioning
confidence: 99%
“…In this seminal paper, the authors introduced a quasi-classical vector model to describe the interaction of two transition dipoles under various geometries. Recently, it has been reported that for a substituted bi-perylene, a dimer which is very similar to BPM, the dihedral angle between the two perylene moieties amounts to B701 [18]. First electronic structure optimisations for BPM arrive at a slightly higher value.…”
Section: Methodsmentioning
confidence: 99%
“…There have only been two previous reports of the application of SCC to this synthesis. [41,42] Borylation of the commercially available 1-bromopyrene 1 and subsequent esterification of the crude free boronic acid 2 with pinacol gave the boronic ester 3 in 80% yield based on 1 (Scheme 1). Compound 3 was prepared on a 25 g scale.…”
Section: Synthesismentioning
confidence: 99%